E-Bus Economics : Fuzzy Math? - Graham, John (International Finance Corporation, Washington, DC, 2020)
Electrifying the global urban vehicle fleet depends on the convergence of several economic, technological, and political factors. However, the big shift to electric vehicles will likely take place only when the economics of owning and operating electric becomes a no-brainer. Using the example of electric buses, two factors must fall into place before the electric option can take off: first, the upfront cost needs to come down and second, there needs to be a change in procurement culture towards lifecycle cost or total cost of ownership (TCO). If utilities can structure out fluctuations in power costs (through PPAs) and the marketplace moves to leasing and other fixed-price operations and maintenance arrangements, these calculations can standardize across the board quickly. This is when the math starts to get a lot less fuzzy.